2019
DOI: 10.1111/1346-8138.15122
|View full text |Cite
|
Sign up to set email alerts
|

Ustekinumab treatment for hidradenitis suppurativa

Abstract: Hidradenitis suppurativa (HS) is a follicular occlusive inflammatory skin disease that occurs in the axilla, groin, buttocks and vulval region. Control of the intractable inflammation is a primary goal of HS treatments. Benefit of anti‐tumor necrosis factor (TNF) antibodies against HS have been reported, and adalimumab has been approved for HS in Europe, the USA and Japan. However, the alternative therapies for anti‐TNF antibodies have not been established yet. We experienced a case of HS which developed durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…In terms of HS therapy, biologic agents, particularly targeting tumour necrosis factor alpha (TNFα), are now an integral part of the management of moderate to severe disease [79][80][81]. Although clinical benefit has been reported with several biologics, including infliximab [82], ustekinumab [83] and secukinumab [84], only adalimumab is licensed at present for the treatment of moderate to severe HS.…”
Section: The Cutaneous And/or Gastrointestinal Microbiomes As a Theramentioning
confidence: 99%
“…In terms of HS therapy, biologic agents, particularly targeting tumour necrosis factor alpha (TNFα), are now an integral part of the management of moderate to severe disease [79][80][81]. Although clinical benefit has been reported with several biologics, including infliximab [82], ustekinumab [83] and secukinumab [84], only adalimumab is licensed at present for the treatment of moderate to severe HS.…”
Section: The Cutaneous And/or Gastrointestinal Microbiomes As a Theramentioning
confidence: 99%
“…8 Candidates for this treatment are young adults (around 35 years of age) with moderate to severe HS, who have previously received multiple treatments for HS. 3 The mean age of our patients was 12 years and all of them had a Hurley stage III HS. All patients had been previously treated with adalimumab, with primary or secondary failure.…”
Section: Discussionmentioning
confidence: 94%
“…Despite of the lack of randomized clinical trials that support the efficacy and safety of ustekinumab in HS, some case reports and case series have been published in the literature [3][4][5][6][7][8][9] ; to the best of our knowledge, 49 cases have been published to date. The dosage used was variable, but most of the patients received the psoriasis dosage regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Ustekinumab is a human monoclonal antibody that acts by inhibiting the p40 subunit on IL-12 and IL-23 [ 127 , 135 ]. In a Phase II open-label study involving 17 patients, patients showed moderate-to-marked improvement achieving HiSCR in almost 40% of cases [ 136 ].…”
Section: Resultsmentioning
confidence: 99%